Nano Online 2016
DOI: 10.1515/nano.bjneah.6.147
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fullerene–Au(111) coupling in (2√3 × 2√3)R30° superstructures with intermolecular interactions

Abstract: This article is part of the Thematic Series "Functional nanostructureselectronic structure, charge and heat transport".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…14 In the (2O3 Â 2O3) R30 structure, all C 60 molecules are in the same orientation. 12,16 The complex chiral motifs have been observed. 17 In CsnC 60 fulleride lms, orientational ordering appears.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…14 In the (2O3 Â 2O3) R30 structure, all C 60 molecules are in the same orientation. 12,16 The complex chiral motifs have been observed. 17 In CsnC 60 fulleride lms, orientational ordering appears.…”
Section: Introductionmentioning
confidence: 94%
“…4 A C 60 monolayer grown on solid surfaces is critical for understanding and controlling the interfacial properties of fullerene-derived electronic and photovoltaic devices. 5,6 STM studies demonstrated that the C 60 monolayer on the solid surface exhibit a variety of lattice orientations such as the "in phase" (2O3 Â 2O3) R30 , [7][8][9][10][11][12][13] , (7 Â 7) R0 13 and (O589 Â O589) R14.5 . [13][14][15] The individual molecules of fullerene and fulleride within a single domain display different orientations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C 60 molecules form various self-assembled structures when deposited on different types of substrate, such as Au [4][5][6][7][8][9], Ag [10][11][12][13][14], Cu [15,16], Pb [17], Pd [18], P [19], Al [20], graphene [21][22][23][24], WSe 2 [25], Si [26][27][28][29], and Ge [30][31][32]. Many results indicate that C 60 molecules are easy to nucleate at the terrace edge and may form a close-packed structure under appropriate conditions, regardless of the types of substrate, such as the 2 √ 3 × 2 √ 3 R30 • domain on Au(111) [33,34] and the 4 × 4 superstructure on graphene/Cu(111) [22].…”
Section: Introductionmentioning
confidence: 99%